O elastyczności organizacji uczącej się - Stańczyk-Hugiet, Ewa (Learning organization's flexibility, 2006)
The paper presents understanding of flexibility as speed and scope of reaction and also shows flexibility mechanisms such as: diversity, redundancy, monitoring, decision making processes simulation and implementation of “organization in motion”. The conclusion is that learning organization is a flexible organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 110-118